Food Consumption Patterns and Trends in Malaysia - Tey, Yeong Sheng (2008)
Since the economic crisis in 1997, there has been notable success in Malaysian economic, where Malaysians are getting wealthier and food consumption is undergoing transitional changes. Thus, it is motivational to gain a better understanding of food consumption patterns and trends in Malaysia. This study intends to investigate food consumption patterns in Malaysia. This is followed by the analyses on the effects of socio-economic factors on food consumption and is further used to do projection for the future food consumption in Malaysia until This study used data from the Household Expenditure Survey (HES) 200412005. Data from the HES was obtained from 14,084 samples in Malaysia. In order to investigate food consumption patterns in Malaysia, this study utilized the methodology of a multi-stage demand system, incorporating demographic variables to estimate income and price elasticities. In order to analyze the effects of socioeconomic factors on food consumption, 36 single equations of Tobit model were estimated. With quantity of food consumed as the dependent variable, the equations were also used to project future consumption of the 36 food items. The estimated positive and inelastic income elasticities show that all the food items are normal goods, except for other meat. Special attention was paid to demand for rice, with positive income elasticity of 0.1325 concerning the question whether rice is an inferior good in Malaysia. While mutton (0.3196), prawn (0.3745), and processed h i t s (0.3088) recorded the highest income elasticity over other food items in the food group respectively. On the other hand, own-price elasticity of each food item shows negative signs, complying with law of demand. Compensated and uncompensated own-price elasticities of rice (-0.5756 and -0.5791) were the lowest in its food group. These results indicate that rice is a necessity and still playing its role as staple food to Malaysians in 200412005. The determinant. of consumption of food items are found to be generally attributed to household income, urbanization, age of household's head, household size, and race. Most of the equations witnessed that gender and employment status of household's head were not significantly related to quantity of food consumed. By taking into account of socio-economic effects, overall projection results show increasing trends for future consumption of the food items, except for rice and other meats.